2018
DOI: 10.1111/jth.14261
|View full text |Cite
|
Sign up to set email alerts
|

Identification of high thrombotic risk triple‐positive antiphospholipid syndrome patients is dependent on anti‐cardiolipin and anti‐β2glycoprotein I antibody detection assays

Abstract: Background The antiphospholipid syndrome (APS) is characterized by thrombosis and/or pregnancy morbidity with the persistent presence of antiphospholipid antibodies (aPL). Triple-positivity (i.e. positivity for lupus anticoagulant [LAC], anti-cardiolipin [aCL] and anti-β2glycoprotein I [aβ2GPI] antibodies) is associated with a high thrombotic risk. Objectives We investigated the variability in triple-positivity detection by measuring the same samples with four commercially available solid phase assays. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 33 publications
(53 reference statements)
5
52
1
1
Order By: Relevance
“…Clinical studies confirm that triple positivity in APS patients and asymptomatic aPL carriers indicates a high risk of recurrence of thrombosis or development of a first thrombotic event, respectively . Although identification of triple positives is dependent on the solid‐phase assay used, the percentage of anti‐DI IgG positives in individuals with distinct antibody profiles were comparable for the four tested solid‐phase assays. In this study, a very good agreement was found between triple positivity and anti‐DI IgG positivity, irrespective of the solid‐phase assay used (Table S5), which is consistent with previous studies .…”
Section: Discussionsupporting
confidence: 90%
“…Clinical studies confirm that triple positivity in APS patients and asymptomatic aPL carriers indicates a high risk of recurrence of thrombosis or development of a first thrombotic event, respectively . Although identification of triple positives is dependent on the solid‐phase assay used, the percentage of anti‐DI IgG positives in individuals with distinct antibody profiles were comparable for the four tested solid‐phase assays. In this study, a very good agreement was found between triple positivity and anti‐DI IgG positivity, irrespective of the solid‐phase assay used (Table S5), which is consistent with previous studies .…”
Section: Discussionsupporting
confidence: 90%
“…In this COVID‐19 cohort, the role of IgA is unclear, without added value on top of the current classification criteria, equally as previously illustrated in APS 10,21,30 …”
Section: Discussionmentioning
confidence: 70%
“…Recent reports indicate the value of this assay in risk management [135] and predicting thrombosis and late pregnancy morbidity [137]. However, as a word of caution, there is variation of results in different commercially available assays [138].…”
Section: Cardiolipinmentioning
confidence: 99%
“…Although the presence of anti-PS/PT antibodies appear to be independent of the LA, they may be a potential substitute for the troubled LA assay [146,147]. The clinical utility of these assays, however, is limited by a paucity of prospective clinical data and lack of standardization [138]. Therefore, additional studies are required before any "noncriteria" immunoassays are included in standard APS classification criteria.…”
Section: Non-criteria Autoantibodies: Phosphatidylserine/prothrombin mentioning
confidence: 99%